Cost-effective optimized scleroglucan production by Sclerotium rolfsii ATCC 201126 at bioreactor scale. A quantity-quality assessment - Valdez, Alejandra Leonor (2021)
Exopolysaccharide (EPS) secretion by Sclerotium rolfsii ATCC 201126 in submerged cultures, already identified as high-osmolarity responsive, was assessed by reducing C-source without compromising EPS yields. A designed medium with 80 g sucrose L−1 (MOPT80) was tested at 3 L-bioreactor scale at different temperature, agitation, aeration and pH (uncontrolled vs. controlled) values. Optimal operative conditions (200 rpm, 28 °C, 0.5 vvm and initial pH -pHi- 4.5) were validated, as well as the possibility to work at pHi 5.5 to reduce biomass production. Purified EPSs produced in MOPT80 at optimal and other valid operative conditions exhibited refined grade (<1 % proteins and ash, 3–4 % reducing sugars, 87–99 % total sugars). EPS purity, MW and rheological parameters led to discourage pH controlled at 4.5. Relatively constant MW (6–8 × 106 Da) and outstanding viscosifying ability were found. Polyphasic EPS analysis (titre, purity, macromolecular features and rheological fitness) would support to properly select production conditions.